Late-onset peripheral joint disease in ankylosing spondylitis. Issue 6 (December 1982) - Cohen, Marc D.; Ginsburg, William W.
Abstract : We reviewed the records of 150 patients with definite ankylosing spondylitis who had significant peripheral arthritis and were seronegative and found 7 patients who had the onset of peripheral arthritis after their spinal disease became inactive. This late-onset peripheral arthritis may lead to significant joint deformity, and aggressive therapy may be warranted.